2014
DOI: 10.18632/oncotarget.2177
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic KIT-induced aggressive systemic mastocytosis requires SHP2/PTPN11 phosphatase for disease progression in mice

Abstract: Acquired mutations in KIT are driver mutations in systemic mastocytosis (SM). Here, we tested the role of SHP2/PTPN11 phosphatase in oncogenic KIT signaling using an aggressive SM mouse model. Stable knock-down (KD) of SHP2 led to impaired growth, colony formation, and increased rates of apoptosis in P815 cells. This correlated with defects in signaling to ERK/Bim, Btk, Lyn, and Stat5 pathways in P815-KD cells compared to non-targeting (NT). Retro-orbital injections of P815 NT cells in syngeneic DBA/2 mice res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…IL-3, c-Kit and IKKs are involved in pathogenesis of a number of malignancies [4345]. Therefore, we determined the activation status of IKKs and their relevance for survival and proliferation in tumor mast cells.…”
Section: Resultsmentioning
confidence: 99%
“…IL-3, c-Kit and IKKs are involved in pathogenesis of a number of malignancies [4345]. Therefore, we determined the activation status of IKKs and their relevance for survival and proliferation in tumor mast cells.…”
Section: Resultsmentioning
confidence: 99%
“…During erythropoiesis, mice harboring a PTPN11 D61Y mutation have been observed to hyper-expand early-stage pro-erythroblasts, with heightened Stat3, Akt and Erk activation also exhibited 122 . In studies by Sharma et al 123, 124 , PTPN11 also has been shown to be a mediator of oncogenic KIT effects on mastocytosis. PTPN11 therefore acts predominantly as an overall positive effector within select type 1 cytokine receptor and RTK systems.…”
Section: ] Potential Targeting Of Signal Transducers Downstream Of Tmentioning
confidence: 97%
“…In EPOR and anemia contexts, targeting PTPN11 is counter-intuitive due to its predominant roles as a positive effector 118, 119, 121, 122, 124 . PTPN11 inhibitors, however, are successfully being developed for candidate use in juvenile myelomonocytic leukemia and Noonan disease 129-131 .…”
Section: ] Potential Targeting Of Signal Transducers Downstream Of Tmentioning
confidence: 99%
“…Moreover, mouse myeloid progenitors and leukaemic cells caused by E76K mutation are sensitive to this inhibitor [54]. Another molecule, II-B08, can inhibit SHP-2 and strongly bind to the receptor [55] and thereby enhances the effects of dasatinib on human and mouse mastocytoma cells.…”
Section: Shp-2mentioning
confidence: 99%